ROLE OF ORAL PANCREATIC ENZYME SUPPLEMENTATION IN PANCREATIC EXOCRINE DEFICIENCY - DESAI, HITENDRA; PATEL, ALPESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The present study was carried out to study the role of oral pancreatic enzyme supplementation in pancreatic exocrine deficiency. Methods: This study included 50 consecutive cases of pancreatic exocrine deficiency. Diagnosis of pancreatic exocrine deficiency was made based on history, clinical examination, and contrast-enhanced computed tomography findings. Each patient was supplied with oral pancreatic enzyme supplements. Each patient was followed up for 1 year with three visits (3 months, 6 months, and 12 months) to assess changes in clinical features of pancreatic exocrine deficiency, change in nutritional status of the patient, and compliance with therapy. Results: At first follow-up visit (3 months), abdominal discomfort reduced in 17 previously symptomatic patients. Mean stool frequency reduced from 3.18 per day to 2.34 per day. Stool consistency improved with only 18 patients (36%) having liquid consistency stool in comparison to 76% at the time of initial presentation. Average body mass index (BMI) improved from baseline value of 20.648 kg/sqm to 20.674 kg/sqm. Average hemoglobin improved from 10.40 g/dL to 10.52 g/dL and average serum albumin remained static at 3.0 g/dL. At second follow-up visit (6 months), abdominal discomfort reduced in 20 previously symptomatic patients. Mean stool frequency reduced from 3.18 per day (primary survey) to 1.7 per day. Stool consistency improved with only 12 patients (24%) having liquid consistency stool in comparison to 76% at the time of initial presentation. Average BMI improved from baseline value of 20.648 kg/sqm to 21.062 kg/sqm. Average hemoglobin improved from 10.40 g/dL to 10.69 g/dL and average serum albumin improved from 3.0 g/dL at primary survey to 3.1 g/dL. At third follow-up visit (12 months), abdominal discomfort reduced in 30 previously symptomatic patients. Mean stool frequency reduced from 3.18 per day (primary survey) to 1.6 per day. Stool consistency improved with only 9 patients (18%) having liquid consistency stool in comparison to 76% at the time of initial presentation. Average BMI improved from baseline value of 20.648 kg/sqm to 21.402 kg/sqm. Average hemoglobin improved from 10.40 g/dL to 10.76 g/dL and average serum albumin improved from 3.0 g/dL at primary survey to 3.3 g/dL. Conclusion: In follow-up visits, there was an improvement in symptoms over 12 months. Abdominal discomfort and stool frequency reduced. Stool consistency improved. Nutritional parameters showed statistically significant improvement. Mean BMI of the study sample, mean hemoglobin, and serum albumin increased. The study provides rationale for using these clinical symptoms as surrogate markers for the efficacy of Pancreatic Enzyme Replacement Therapy in patients with pancreatic exocrine insufficiency.